1995
DOI: 10.1046/j.1471-4159.1995.64010229.x
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral Dialysis and the Blood‐Brain Barrier

Abstract: The aim of the study was to evaluate how implantation of a dialysis probe influences the blood-brain barrier. Leakage of endogenous serum albumin was evaluated by Evans blue/albumin staining and by immunohistochemistry . The passage from blood to dialysate of two substances that normally do not pass into the brain, [3H]inulin and glutamate, was studied 3 and 24 h after insertion of a dialysis probe. Evans blue, given 20 min before rats were killed, was observed around the probe and surrounding brain tissue . A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(27 citation statements)
references
References 9 publications
0
27
0
Order By: Relevance
“…As shown in Figures 4a through 4d, albumin failed to cross the intact BBB (Figures 4e through 4h). In contrast, after mechanically induced BBB breakdown, 20 extravasation of albumin in the brain parenchyma was observed as a positive control (Figures 4i through 4l). In addition, Figures 4m and 4n, which include GFAP immunostaining, show that the tPA that crosses the intact BBB diffuses at a distance up to that of the astrocytic end feet.…”
Section: Benchenane Et Al Tpa An Interface Between Brain and Blood 2mentioning
confidence: 97%
See 1 more Smart Citation
“…As shown in Figures 4a through 4d, albumin failed to cross the intact BBB (Figures 4e through 4h). In contrast, after mechanically induced BBB breakdown, 20 extravasation of albumin in the brain parenchyma was observed as a positive control (Figures 4i through 4l). In addition, Figures 4m and 4n, which include GFAP immunostaining, show that the tPA that crosses the intact BBB diffuses at a distance up to that of the astrocytic end feet.…”
Section: Benchenane Et Al Tpa An Interface Between Brain and Blood 2mentioning
confidence: 97%
“…Mechanically induced BBB breakdown for positive control was performed as described by Westergren and colleagues. 20 …”
Section: Fitc Injection and Confocal Microscopy For Determination Of mentioning
confidence: 99%
“…The significant volume of tissue damage surrounding the microdialysis probe (Clapp-Lilly et al, 1999) could dramatically increase the distance between the probe tip and undamaged, transporter-expressing astrocytic membrane. We speculate that this transporter-free space surrounding the microdialysis probe, along with damage to the blood-brain barrier (Westergren et al, 1995), allows for buildup of extracellular glutamate and results in an artificially high ambient glutamate estimate. Our data support this speculation by showing that acutely blocking transport with TBOA increased the ambient glutamate concentration, even in conditions in which neuronal activity was blocked.…”
Section: Glutamate Transport Is Highly Efficientmentioning
confidence: 99%
“…Microdialysis, characterized as a minimal invasive technique, causes local tissue damage and perturbation of the BBB function. Several studies have reported relatively (within hours) fast restoration of the BBB following the insertion of the microdialysis probe (Benveniste et al, 1989;Dykstra et al, 1992;de Lange et al, 1995), whereas other reports call for a caution when using microdialysis to study normal BBB function (Westergren et al, 1995;Morgan et al, 1996;Groothuis et al, 1998). The latter reports suggest that microdialysis may overestimate the rate of drug transfer Fig.…”
Section: Resultsmentioning
confidence: 99%